FINANCIAL FEASIBILITY STUDY OF MIX-USE BUILDING AREA INVESTMENT PLAN - Sandy Putri (NIM: 29115550), Nurul
PT KLM owns a land located in one of big cities in West Java Province. Located in strategic location, PT KLM wants to maximize the utilization of the land and propose a business agreement to PT Wijaya Karya (WIKA) to develop it into an area consisting of several buildings with different functions (mixuse building area). The area is planned to have 9 businesses; 4-star hotel, convention center, co-living apartment, sport center, school, co-working space, parking building, and theme park. The cooperation or business agreement between PT KLM and WIKA is Kerja Sama Usaha (KSU) with a 30 years consortium time. The development of this area requires considerable investment cost. For that, further analysis should be conducted. This research is intended to conduct financial feasibility analysis of investment plan of this mix-use building area as consideration to WIKA the prospective investor of this investment. Through this research, author analyze the feasibility of this investment plan by calculating the required operational cost, revenue, and other expenses. The feasibility of an investment plan can be financially analyzed by using Discounted Cash Flow (DCF) method. Author calculate number of DCF parameters which are Net Present Value (NPV), Internal Rate of Return (IRR), and Payback Period (PP). In order to reduce uncertainty from the calculation, the financial projection is performed by using 3 scenarios; moderate, pessimistic, and optimistic. In addition, author also conducted a sensitivity test of 53 variables to determine which variable is most affected to the NPV and IRR of the project. From the results of financial projections, the development of mix-use building area required Rp 957 Billion. WIKA also need to pay a compensation fee as much as Rp 555 Billion within first 10 years of the consortium time. With WACC 11.51%, using the basic assumption (moderate scenario) the NPV of this investment is Rp 65.4 Billion, IRR 12.92%, and 26 years of payback period. From the sensitivity analysis, there are 4 variables that greatly affect the NPV and IRR, which are total investment cost (capital expenditure), hotel operating cost, theme park operating cost, and total compensation fee.